LAST DECADE OF GREEN LOGISTICS WITH MULTIPLE MODES OF TRANSPORTATION: A LITERATURE REVIEW - Temizceri, Talya; Kara, Selin Soner (POZNAN SCH LOGISTICS, 2023)
Background: Transportation systems with multiple modes are effective, economical, and also offer environmental benefits. This paper summarizes the contributions of multimodal and intermodal transportation systems to the progress in green logistics from 2012 to 2022. A literature survey was conducted to determine the characteristic problems in developing sustainable logistics as well as the techniques and approaches to solve them. The study identified research gaps, and the outcomes will provide a reference for researchers in future work. Published work regarding environmental issues, mode combinations, problem formulations, and solution approaches were evaluated. Research gaps were also identified, and the main requirements for future research were proposed. It was shown that intermodal and multimodal transportation problems in the field of green logistics have received substantial attention in existing literature. However, this is the first literature review of the topic that has considered the body of literature published in the last decade. Methods: The researchers conducted a literature survey to gather relevant information on the topic, based on searching and reviewing academic papers, research articles, conference proceedings, and other publications related to multimodal and intermodal transportation systems and their impact on green logistics from 2012 to 2022. The phases of research method followed data collection, data evaluation, identification of research gaps, proposal of main requirements, and offering valuable insights for future research endeavors. Results: The result of this study highlights the key findings, such as increasing focus on environmental consideration in multiple mode of transportation, lack of studies on uncertainty, utilizing sophisticated solution techniques, the need for different mode combinations, and integrating technological developments to the transportation systems. Conclusions: This study shows that while there is a rich body of literature on multimodal and intermodal transportation systems, the focus has predominantly been on economic rather than environmental sustainability. Future research should prioritize environmentally sustainable multi/intermodal transportation systems, exploring multi-objective planning, integrating different vehicle types, and improving meta-heuristics to tackle real-world logistics challenges.
Keywords: Environmental impact of transportation; Multimodal transportation systems; Intermodal transportation systems; Green logistics; Comprehensive literature review; FREIGHT TRANSPORT; INTERMODAL TRANSPORTATION; HAZARDOUS MATERIALS; OPTIMIZATION APPROACH; NETWORK; SERVICE; TIME; ROAD; LOCATION; DESIGN; Business & Economics